2021
DOI: 10.1111/1754-9485.13291
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID‐19 pandemic on diagnostic imaging services in Australia

Abstract: Introduction The COVID‐19 pandemic is driving unprecedented changes in healthcare services worldwide. This study aimed to quantify the impact of the first wave of the COVID‐19 pandemic on diagnostic imaging services in Australia using an interrupted time series model. Methods Monthly data were extracted from the Australian Medicare Benefits Schedule for all diagnostic imaging services performed between January 2016 and December 2019. Holt‐Winters forecasting models were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
(80 reference statements)
1
7
0
1
Order By: Relevance
“…Nuclear medicine was the modality most impacted. This is less than the data obtained from Medicare reported by Sreedharan et al [ 12 ], who found that general radiography and ultrasound were most impacted, while computed tomography and nuclear medicine services were less affected. It was unclear whether paediatric data were included in their analysis[ 12 ].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Nuclear medicine was the modality most impacted. This is less than the data obtained from Medicare reported by Sreedharan et al [ 12 ], who found that general radiography and ultrasound were most impacted, while computed tomography and nuclear medicine services were less affected. It was unclear whether paediatric data were included in their analysis[ 12 ].…”
Section: Discussionmentioning
confidence: 55%
“…To our knowledge, little is known about the severity of impact on radiology volumes in Australia. While overall Australian imaging volumes were analysed through Medicare, no institutional experience has been presented[ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,3,5 The only exception was during 2020, during which there was a decrease in imaging services attributed to the COVID-19 pandemic and associated lockdown measures. 15 Total imaging services as a proportion of total Medicare services also steadily increased over the study period. This suggests that the growth in imaging services is outpacing the growth in the overall healthcare demand in Australia, further demonstrating the increasing utility of radiology in the evolving practice of clinical medicine.…”
Section: Discussionmentioning
confidence: 90%
“…Most guidelines for performing PET-CT during the pandemic stated that 18-fluorodeoxyglucose (FDG) PET-CT for staging or therapy response assessment should not be postponed in patients without known active COVID-19 infection [ 19 ]. In fact, the workload in nuclear medicine departments was less affected by the initial worldwide lockdown (between March and May 2020) than other imaging modalities, with rebound resurgence in scan numbers in the following months [ 20 ]. A study conducted in 7 US medical centers found that PET-CT specifically was consistently the least impacted imaging modality, with a drop of 16% in patient output, more pronounced in centers located at pandemic outbreak locations [ 21 ].…”
Section: Challenges In Imaging Patients With Hematological Malignanci...mentioning
confidence: 99%